Indole alkaloids inhibit zika and chikungunya virus infection in different cell lines (2021)
Abstract Background In recent years, an increase in the occurrence of illnesses caused by two clinically- important arboviruses has been reported: Zika virus (ZIKV) and Chikungunya virus (CHIKV). There is no licensed antiviral treatment for either of the two abovementioned viruses. Bearing in mind that the antiviral effect of indole alkaloids has been reported for other arboviral models, the present study proposed to evaluate the antiviral in vitro and in silico effects of four indole alkaloids on infections by these two viruses in different cell lines. Methods The antiviral effects of voacangine (VOAC), voacangine-7-hydroxyindolenine (VOAC-OH), rupicoline and 3-oxo voacangine (OXO-VOAC) were evaluated in Vero, U937 and A549 cells using different experimental strategies (Pre, Trans, Post and combined treatment). Viral infection was quantified by different methodologies, including infectious viral particles by plating, viral genome by RT-qPCR, and viral protein by cell ELISA. Moreover, molecular docking was used to evaluate the possible interactions between structural and nonstructural viral proteins and the compounds. The results obtained from the antiviral strategies for each experimental condition were compared in all cases with the untreated controls. Statistically significant differences were identified using a parametric Student’s t-test. In all cases, p values below 0.05 (p < 0.05) were considered statistically significant. Results In the pre-treatment strategy in Vero cells, VOAC and VOAC-OH inhibited both viral models and OXO-VOAC inhibited only ZIKV; in U937 cells infected with CHIKV/Col, only VOAC-OH inhibited infection, but none of the compounds had activity in A549 cells; in U937 cells and A549 cells infected with ZIKV/Col, the three compounds that were effective in Vero cells also had antiviral activity. In the trans-treatment strategy, only VOAC-OH was virucidal against ZIKV/Col. In the post-treatment strategy, only rupicoline was effective in the CHIKV/Col model in Vero and A549 cells, whereas VOAC and VOAC-OH inhibited ZIKV infection in all three cell lines. In the combined strategy, VOAC, VOAC-OH and rupicoline inhibited CHIKV/Col and ZIKV/Col, but only rupicoline improved the antiviral effect of ZIKV/Col-infected cultures with respect to the individual strategies. Molecular docking showed that all the compounds had favorable binding energies with the structural proteins E2 and NSP2 (CHIKV) and E and NS5 (ZIKV). Conclusions The present study demonstrates that indole alkaloids are promising antiviral drugs in the process of ZIKV and CHIKV infection; however, the mechanisms of action evaluated in this study would indicate that the effect is different in each viral model and, in turn, dependent on the cell line.